2021
DOI: 10.4103/jpbs.jpbs_531_20
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Double Antibiotic Paste and Amoxicillin-Clavulanate Paste Used in Endodontic Regeneration on Microhardness of Radicular Dentine: An In vitro Study

Abstract: Objective: Double antibiotic paste is a root canal medicament used in regenerative endodontics and its long-term exposure to dental hard tissues was shown to reduce its mechanical properties. The amoxicillin-clavulanate paste is a medicament effective against endodontic pathogens and is effective in endodontic regeneration. Its effect on radicular dentine is yet to be investigated. The purpose of this study is to investigate and compare the effects of double antibiotic paste and amoxicillin-clavul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This content is excluded in DAP (metronidazole and ciprofloxacin), which is still adequately efficient against E. faecalis and Porphyromonas gingivalis [ 9 , 10 ], and indicated in case of failure of commonly-used medicaments [ 1 ]. However, while even short-term application of antibiotic combinations (as in TAP and DAP) can increase the risk of antibacterial resistance, long-term exposure to DAP may cause demineralization and negatively affect the mechanical properties of dental hard tissues [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This content is excluded in DAP (metronidazole and ciprofloxacin), which is still adequately efficient against E. faecalis and Porphyromonas gingivalis [ 9 , 10 ], and indicated in case of failure of commonly-used medicaments [ 1 ]. However, while even short-term application of antibiotic combinations (as in TAP and DAP) can increase the risk of antibacterial resistance, long-term exposure to DAP may cause demineralization and negatively affect the mechanical properties of dental hard tissues [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of E. faecalis to form biofilms could also confer up to 1,000 times stronger resistance against antibiotic agents than in planktonic conditions 4,5) . Many researchers have performed experiments to eliminate E. faecalis from the root canal and prevent E. faecalis reinfection using various antibacterial materials, including nanoparticles [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…9 , 10 Some other studies have removed minocycline from the combination without any replacements for the drug; however, the double antibiotic paste comprising ciprofloxacin and metronidazole lack the antibacterial activity related to minocycline. 11 In a recent study, a novel combination of triple antibiotics was introduced (penicillin G, metronidazole, and ciprofloxacin; PMC), which exhibited a wide range of antibacterial activity with penicillin G as one of its components affecting Enterococcus faecalis , a dominant microorganism found in endodontic failure. Moreover, the combination revealed acceptable antibiotic activity against other prevailing intracanal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, modifications of TAP (mTAP), with cefaclor, amoxyclav, clindamycin, and amoxicillin as possible replacements for minocycline, have been studied; nevertheless, related research has reported degrees of tooth discoloration immediately or after a time period of using mTAP 9,10 . Some other studies have removed minocycline from the combination without any replacements for the drug; however, the double antibiotic paste comprising ciprofloxacin and metronidazole lack the antibacterial activity related to minocycline 11 . In a recent study, a novel combination of triple antibiotics was introduced (penicillin G, metronidazole, and ciprofloxacin; PMC), which exhibited a wide range of antibacterial activity with penicillin G as one of its components affecting Enterococcus faecalis , a dominant microorganism found in endodontic failure.…”
Section: Introductionmentioning
confidence: 99%